SPE International Symposium on Oilfield Chemistry 2001
DOI: 10.2118/65019-ms
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of First and Multiple Contact Carbon Dioxide Induced Asphaltene Precipitation

Abstract: Precipitation of solids, believed to be asphaltenes is common in most carbon dioxide floods. The oils in most carbon dioxide flood applications, however, are light crudes with low initial asphaltene content. Precipitation is common after carbon dioxide breakthrough in production equipment. It is believed that precipitation does not occur in the reservoir. The objective of this paper was to identify the reasons for this phenomenon. The mature carbon dioxide flood at Rangely field in Colorado was selected as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The increase of asphaltene risks through gas injection has been recognized as a general rule (Kokal et al 2003;Srivastava et al 1999;Parra-Ramirez et al 2001;Sarma 2003;Jamaluddin et al 2000;Kokal et al 2004;Negahban et al 2005;Okwen 2006; Moghadasi et al 2006). A preparatory evaluation of asphaltene behavior under gas-mixing conditions is important to minimize risks and to optimize the gas-injection project.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of asphaltene risks through gas injection has been recognized as a general rule (Kokal et al 2003;Srivastava et al 1999;Parra-Ramirez et al 2001;Sarma 2003;Jamaluddin et al 2000;Kokal et al 2004;Negahban et al 2005;Okwen 2006; Moghadasi et al 2006). A preparatory evaluation of asphaltene behavior under gas-mixing conditions is important to minimize risks and to optimize the gas-injection project.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a CO 2 flood in the Midale reservoir in southeastern Saskatchewan showed that a considerable amount of solid deposit (consisting of asphaltenes, wax, and trapped oil) formed in the wellbore equipment and downhole facilities shortly after CO 2 breakthrough in the production wells . Similar problems were reported in many other oil fields with CO 2 EOR operations across the world. Over longer time scales, the phenomenon of selective dissolution is a potential problem because this can negatively impact CO 2 injectivity, sweep efficiency, and incremental oil production.…”
Section: Introductionmentioning
confidence: 91%
“…Some of the significant parameters involved in the asphaltene deposition phenomenon are asphaltene onset pressure (AOP), lower and upper asphaltene envelope, reservoir pressure, and bubble point pressure. Gas injection is one of the most common EOR approaches that increases ultimate oil recovery in many cases because of induced oil viscosity reduction or pushing the oil toward the wellbore . One of the most effective agents in this type of EOR method is natural gas, which leads to increased oil production, although the natural gas injection into an oil reservoir could change the flow behavior and the fluid equilibrium properties, which cause asphaltene precipitation and deposition problems. , Despite several decades of research and development projects, gas-induced asphaltene deposition is still a major flow assurance challenge. , There are different approaches for asphaltene remediation and inhibition, including mechanical techniques (pigging, mechanical/manual striping, and mechanical vibration , ), chemical treatments (dispersants, antifoulants, coagulants, and polar co-solvents ), and thermal techniques (steam injection, hot chemical injection, microwave technique, and in situ combustion). Between all of these techniques, chemical injection is one of the most widely used strategies to tackle the asphaltene precipitation and deposition barrier. , Millions of dollars per year are estimated to be spent each year on installing and servicing asphaltene mitigation equipment and chemicals .…”
Section: Introductionmentioning
confidence: 99%